All Days 2005
DOI: 10.2118/94437-ms
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum-Based HPWBM Successfully Replaces Oil-Based Mud To Drill Exploratory Wells in an Environmentally Sensitive Area

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 9 publications
0
6
0
2
Order By: Relevance
“…(Marin, J., 2009;Cameron, C., 2001;Hodder, M., 2006;Ramirez, M.A., 2005). This kind of drilling fluid demonstrated excellent performance and also contributed to the project success by minimizing non-productive time (NPT) and costs related to fluid/cuttings disposal.…”
Section: Design Of Drilling Fluid For 12 1/4 In Sectionmentioning
confidence: 99%
“…(Marin, J., 2009;Cameron, C., 2001;Hodder, M., 2006;Ramirez, M.A., 2005). This kind of drilling fluid demonstrated excellent performance and also contributed to the project success by minimizing non-productive time (NPT) and costs related to fluid/cuttings disposal.…”
Section: Design Of Drilling Fluid For 12 1/4 In Sectionmentioning
confidence: 99%
“…Ostatnio zaproponowano wiele rozwiązań stabilizowania formacji łupkowych, między innymi stosowanie w składach płuczek wiertniczych węglanu wapnia o różnym stopniu granulacji, asfaltenów, poliglikoli czy akrylanów [3,5,13,17,20]. Badania prowadzone w celu ograniczenia ciśnienia porowego skał łupkowych wykazały, że stosowane środki w płuczkach wiertniczych, takie jak zmodyfikowany węglan wapnia, akrylany i polimery, nie zapobiegają wzrostowi ciśnienia porowego z uwagi na zbyt duże rozmiary, niedostosowane do wielkości porów skały łupkowej (< 0,01 μm).…”
unclassified
“…Lateks w zaczynie cementowym służy głównie do kontrolowania filtracji oraz ograniczania migracji gazu. W składach płuczek wiertniczych dodatek lateksu powinien wpływać na zmniejszenie filtracji poprzez wytwarzanie na powierzchni skał łupkowych odkształcalnego uszczelnienia, ograniczającego wzrost ciśnienia porowego skał łupkowych [1, 6,11,13,21].…”
unclassified
“…synthetic-based (SBM). Technically, OBM and SBM drilling fluids are the best suited for drilling shale formations because they don't interact with shale (Ramirez, et al 2005). They provide stability of borehole and cuttings, and efficient solids removal.…”
Section: Resistivitymentioning
confidence: 99%
“…Few published work related to aluminum/precipitating chemistry in drilling fluids, since pore pressure transmission measuring techniques have been only developed recently (Stowe, et al 2001) . Nonetheless, the aluminum chemistry in drilling fluids has been applied in Louisiana USA, Gulf of Mexico, South America, Norway, and Algeria (Halliday, et al 1993) (Ramirez, et al 2005 Hydration and pore-pressure transmission tests were performed on the samples with different drilling fluids. Their studies showed that the use of aluminum complex in water resulted in 12% hydration, whereas it was 50% in fresh water.…”
Section: Previous Workmentioning
confidence: 99%